2010
DOI: 10.1016/j.jbtep.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Personality and early maladaptive schemas: A five-factor model perspective

Abstract: According to Young's schema model (Young, J. E., Klosko, J. S., & Weishaar, M. E. (2003). Schema therapy: A practitioner's guide. New York: Guilford Press), innate personality tendencies are important for the understanding of early maladaptive schemas (EMS). The current study examined the relations between EMS and the dimensions of the five-factor model of personality (FFM). One hundred and forty-seven adult outpatients completed the NEO PI-R, the Schema Questionnaire-Short Form (SQ-SF), and the Beck Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
18

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 59 publications
6
45
0
18
Order By: Relevance
“…These findings are consistent with other results reported in researches made by Muris [4], Sava [5], Thimm [6] and others. We chose to relate to these studies because the tools and the research approach are similar in terms of both sample and design,…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These findings are consistent with other results reported in researches made by Muris [4], Sava [5], Thimm [6] and others. We chose to relate to these studies because the tools and the research approach are similar in terms of both sample and design,…”
Section: Discussionsupporting
confidence: 94%
“…Schemas in this domain often emerge when the early family environment is enmeshed, undermining of the child's confidence, overprotective, or failing to reinforce the child for performing competently outside the family. There are four schemas of this domain: 1 (6). Dependence/Incompetence, 2(7).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that GAD is strongly associated with personality disorders (36), and from a clinical and comorbidity point of view, GAD is also similar to emotional disorders, namely depression (18). For instance, regarding depressive symptoms, an association has been found between high Neuroticism and low Extraversion, and the presence of MCS (37). Two schemas are mainly involved here, namely Emotional Deprivation and Abandonment/Instability (38).…”
Section: Discussionmentioning
confidence: 92%
“…In a clinical research done by Young and Brown on patients with more depression, it was detected that the total score of Young and Brown's EMSs questionnaire had a correlation with the severity of depression symptoms, even after controlling the neurotic and other personality traits (25). It was declared that EMSs show the higher variance in depression severity than structures like this character which is detected as dependent to depression symptom such as Neuroticism (26). In another clinical case with depression symptoms, Petrocelli et al revealed that schemas of abandonment / instability, defectiveness / shame, failure to achieve, compliance, and vulnerability to injury have a cross-sectional relationship with depression severity (27).…”
Section: Introductionmentioning
confidence: 99%